ANALISIS SEMIOTIKA PESAN MORAL DALAM DRAMA KOREA “ITAEWON CLASS” - Inggrit Febriani Pardede; Elok Perwirawati; Shabrina Harumi Pinem (JURNAL SOCIAL OPINION: Jurnal Ilmiah Ilmu Komunikasi, 2021)
This research is entitled Semiotic Analysis of the Moral Message of the Korean Drama Itaewon Class. By understanding a semiotic analysis to feel something strange and something that needs to be questioned further when reading a certain text or narrative, the Semiotics used is Roland Barthes' semiotics. According to Barthes, everything that is fixed, steady, stable, is a myth. The purpose of this study is to analyze the construction of communication messages in the Korean Drama Itaewon Class and the semiotic aspects of the moral message. The research method used is qualitative research. This study uses a constructivist paradigm that is antithetical to the notion that puts observation and objectivity in finding a reality. Korean dramas are dramas that describe the lives of Korean people with stories that involve various conflicts and are broadcast within a certain time interval. Meanwhile, semiotics in Korean films may still be considered too young when compared to Hollywood, which was a pioneer in the film industry. By looking at the development of cinematography, we can see that Korean cinema is gradually catching up to the success of the Hollywood film industry. The results of the study show that the moral message is something good that is adjusted to the measures of action that are generally accepted, including certain social or environmental units.